Utility of a dual immunostain cocktail comprising of p53 and CK20 to aid in the diagnosis of non-neoplastic and neoplastic bladder biopsies - Dhir Rajiv; Bastacky Sheldon; Armah Henry B; Recavarren Rosemary; Yildiz Isil Z; Parwani Anil V (BMC, 2009)
Abstract Background Distinction between non-neoplastic and neoplastic bladder lesions is therapeutically and prognostically important. Our objective is to describe the use of double immunohistochemistry (DIHC) for p53+CK20 as a tool for diagnosing neoplasia in bladder biopsies. Methods p53+CK20 DIHC were examined in 38 reactive atypia, 10 dysplasia, 9 carcinoma in situ (CIS) and 7 invasive carcinoma (IC) cases. CK20 was evaluated according to distribution extent and degree of intensity whereas percentage of positive cells together with staining intensity was taken into account in the evaluation of p53. Results 92% of reactive cases were either CK20(-) or (+) only in the upper 1/3 urothelium. In dysplastic cases CK20 staining distribution was as follows: 60% in 2/3 of the urothelium, 30% full thickness, 10% in the upper 1/3 urothelium. Among CIS cases, 89% had full thickness CK20 positivity, of which 62% were p53(+). 71% of IC cases exhibited strong and full thickness dual staining. Conclusion This is the first study in the literature to use DIHC of p53+CK20 in distinction of non-neoplastic and neoplastic bladder lesions. Dual staining by p53+CK20 cocktail allows for histologic correlation and diminishes the risk of losing the area of interest in limited biopsy specimens.